Case report: Primary familial brain calcification associated with a rare PDGFRB variant, coexisting with nontraumatic osteonecrosis of the femoral head - Cao, Conghui; Luo, Jing; Wang, Xiaoli (Frontiers in Neuroscience, 2024)
Primary familial brain calcification (PFBC) is a rare genetic neurodegenerative disorder characterized by bilateral calcifications in the brain. PFBC may manifest with a broad spectrum of motor, cognitive, and neuropsychiatric symptoms. Several causal genes have been identified in PFBC, which are inherited as both autosomal dominant and autosomal recessive traits. Herein, we present the case of a Chinese family diagnosed with PFBC. The family members carry a rare heterozygous variant (p. R334Q) in exon 7 of platelet-derived growth factor receptor β (PDGFRB) gene. The platelet-derived growth factor-B/PDGF receptor β (PDGF-B/PDGFRβ) signaling pathway plays a crucial role in pericyte development in various organs and tissues. Notably, this variant uniquely coexists with nontraumatic osteonecrosis of the femoral head. Additionally, we reviewed previous studies on PFBC-causing variants in PDGFRB.